Conversion Crude Palm Oil to FAME Over ZnO Catalyst Presipitant Zinc Carbonate - Sahan, Yusnimar; Heliyanti, Sri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Crude palm oil has a high free fatty acid over 2% is called CPO off-grade. This oil as an alternative energy sources are less costly in the held in one stage by a heterogeneous catalyst in order to produce a biodiesel or fatty acid methyl ester (FAME) over a ZnO catalyst. In this research, ZnO is made from zinc carbonate precipitant. Yield of conversion oil to FAME found approximately 96% under condition temperatures reaction 65 ±2°C, ratio moles of reactants 1:18 v/v, and the amount of catalyst 0.5%. ZnO catalyst is found as a potential in the biodiesel production. The catalytic activity of catalyst is determined by regenerating the spent catalyst, then it re-used four times in the transesterification reaction cycles. Results, the catalytic activity of ZnO catalyst till retain in the 4 th reaction cycle giving the yield of crude biodiesel in the range of 96 –75 %.